Furnace and Fugue : A Digital Edition of Michael Maier's Atalanta fugiens (1618) with Scholarly Commentary - University Press of Virginia; Nummedal, Tara E.; Bilak, Donna (2021)
"Furnace and Fugue brings to life in digital form an enigmatic seventeenth-century text, Michael Maier’s alchemical emblem book Atalanta fugiens. This intriguing and complex text from 1618 reinterprets Ovid’s legend of Atalanta as an alchemical allegory in a series of fifty emblems, each of which contains text, image, and a musical score for three voices. Re-rendering Maier’s multimedia masterpiece as an enhanced digital publication, Furnace and Fugue allows contemporary readers to hear, see, manipulate, and investigate Atalanta fugiens in ways that were perhaps imagined when it was composed but were simply impossible to realize in full before now." [self-description]